Regulation and risk shuffling in bank securities portfolios - Andreas Fuster; James Vickery (Federal Reserve Bank of New York, 2018)
Bank capital requirements are based on a mix of market values and book values. We investigate the effects of a policy change that ties regulatory capital to the market value of the "available-for-sale" investment securities portfolio for some banking organizations. Our analysis is based on security-level data on individual bank portfolios matched to bond characteristics. We find little clear evidence that banks respond by reducing the riskiness of their securities portfolios, although there is some evidence of a greater use of derivatives to hedge securities exposures. Instead, banks respond by reclassifying securities to mitigate the effects of the policy change. This shift is most pronounced for securities with high levels of interest rate risk.
Keywords: G21; G23; G28; 330; bank; securities; available-for-sale; capital regulation; fair value accounting